2014
DOI: 10.1542/peds.2013-1922
|View full text |Cite
|
Sign up to set email alerts
|

Violent Film Characters’ Portrayal of Alcohol, Sex, and Tobacco-Related Behaviors

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Youth are frequent consumers of movies that contain high levels of violence, and violent content in films, especially those rated PG-13, has been increasing over time.WHAT THIS STUDY ADDS: Content analyses seldom examine how violence is portrayed with other health risk behaviors, such smoking, drinking, and sex. This study presents an innovative way to characterize on-screen violent content and demonstrates the extent to which risk behaviors co-occur within films. abstract OBJECTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…The final sample included 29 mainstream films and 34 Black-oriented films (one film originally coded with mainstream films ( Ride Along ) met the criterion for a predominately Black cast). Exposure to sexual content was calculated only for R-rated films ( n =7 mainstream; n =16 Black-oriented ) because most explicit sex content is found in R-rated films; the MPAA rating system is less effective in restricting violent and alcohol content, which appear equally in PG-13 and R-rated films (Bleakley, Romer, & Jamieson, 2014; Nalkur, Jamieson, & Romer, 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample included 29 mainstream films and 34 Black-oriented films (one film originally coded with mainstream films ( Ride Along ) met the criterion for a predominately Black cast). Exposure to sexual content was calculated only for R-rated films ( n =7 mainstream; n =16 Black-oriented ) because most explicit sex content is found in R-rated films; the MPAA rating system is less effective in restricting violent and alcohol content, which appear equally in PG-13 and R-rated films (Bleakley, Romer, & Jamieson, 2014; Nalkur, Jamieson, & Romer, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…The films were coded by trained coders in five-minute segments ( n =1,510) using a directed, quantitative, previously-validated coding scheme (Bleakley, Jamieson, & Romer, 2012; Bleakley et al, 2014; Jamieson & Romer, 2008; Nalkur et al, 2010). After multiple training sessions, the coders achieved inter-coder reliability for identifying the presence of each behavior as calculated by Krippendorff's alpha using a separately validated test sample of 59 segments.…”
Section: Methodsmentioning
confidence: 99%
“…The films were coded in their entirety by five trained coders in five-minute segments ( n = 1,510) using a directed, quantitative, previously-validated coding scheme (Bleakley et al, 2012, 2014; Jamieson & Romer, 2008; Nalkur et al, 2010). After multiple sessions of training, the coders achieved inter-coder reliability as calculated by Krippendorff’s alpha using a separate, previously validated test sample of 59 segments before coding the films independently.…”
Section: Methodsmentioning
confidence: 99%
“…A content analysis of reality television found that alcohol use was correlated with sexual behavior and tobacco use (Flynn, Morin, Park, & Stana, 2015). Another study found that more than three quarters of popular films involved a violent character engaging in at least one other risk behavior (Bleakley, Romer, & Jamieson, 2014). …”
mentioning
confidence: 99%
“…Content analyses of popular media such as movies and television demonstrate that these behaviors tend to cluster onscreen just as they often do in adolescent behavior (Bleakley, Romer, & Jamieson, 2014; Flynn, Morin, Park, & Stana, 2015). Despite the widespread popularity of social media, television and film content remain an important source of envrionmental influences.…”
Section: Introductionmentioning
confidence: 99%